Addition of Neostigmine and Tramadol to 1.5 % Lidocaine for paracervical block to reduce post-operative pain in colporrhaphy - Alireza Kamali; Maryam Shokrpour; Bijan Yazdi; Atefeh Khalilpour (PAGEPress Publications, 2018)
Pain is a complex and multi-faceted human perception and several factors could dampen the pain. Therefore, we aimed to comparison of addition of neostigmine and tramadol to 1.5 % lidocaine with paracervical block in reduce of post-operative pain in colporrhaphy. This study was a randomized and double-blind clinical trial for 108 patients' as candidate for colporrhaphy. Patients were randomly divided in three groups (Neostigmine, tramadol and control).We recorded pain in 2 and 6 and 12 hours after surgery, duration of analgesia and mean of use narcotic drug in 24 hours after surgery for all patients. Mean of narcotic drug used in 24 hours after surgery in neostigmine group was more than tramadol group(p=0/01).Pain in 2 and 6 and 12 hours after surgery in neostigmine group was more than tramadol group (p=0/01). Duration of analgesia in tramadol group was over neostigmine group and also, it was in neostigmine group was more than placebo (p=0/01).Taken together, tramadol could reduce pain in 2 and 6 and 12 hours after surgery and mean of narcotic drug used in 24 hours after surgery and increase duration of analgesia.